The Design of Memories. Art and Technology for Teacher Education - Huerta, Ricard (2024)
We present an artistic research developed with university students. Under the theme of memories and the idea “Machines have memory, people have memories”, an exhibition was presented at the Computer Museum with the title “The design of memories”, with 22 artistic installations made by students, establishing a dialogue with the museum’ collection. The research seeks pedagogical alternatives from art education, incorporating approaches that investigate social, political and cultural aspects, such as museums, as well as collective creation formats. It is presented as a case study, incorporating teaching narratives, questionnaires, and Arts-Based Research. The positive evaluation of the exhibition leads us to consider this activity as an enriching model in artistic and heritage education, promoting creativity and collaborative work.